Longer prostate stromal cell telomere length is associated with increased risk of death from other cancers - Mori, Joakin O.; Platz, Elizabeth A.; Lu, Jiayun; Brame, Alexandria; Han, Misop; Joshu, Corinne E.; De Marzo, Angelo M.; Meeker, Alan K.; Heaphy, Christopher M. (Frontiers in Medicine, 2024)
Background: Telomeres are located at chromosomal termini and function to maintain genomic integrity. Telomere dysfunction is a well-recognized contributor to aging and age-related diseases, such as prostate cancer. Since telomere length is highly heritable, we postulate that stromal cell telomere length in the tissue of a particular solid organ may generally reflect constitutive stromal cell telomere length in other solid organs throughout the body. Even with telomere loss occurring with each round of cell replication, in general, telomere length in prostate stromal cells in mid-life would still be correlated with the telomere length in stromal cells in other organs. Thus, we hypothesize that prostate stromal cell telomere length and/or telomere length is a potential indicator of the likelihood of developing future solid cancers, beyond prostate cancer, and especially lethal cancer.To explore this hypothesis, we conducted a cohort study analysis of 1,175 men who were surgically treated for prostate cancer and were followed for death, including from causes other than their prostate cancer.In this cohort study with a median follow-up of 19 years, we observed that longer prostate stromal cell telomere length measured in tissue microarray spots containing prostate cancer was associated with an increased risk of death from other solid cancers. Variability in telomere length among these prostate stromal cells was possibly positively associated with risk of death from other solid cancers.Studying the link between stromal cell telomere length and cancer mortality may be important for guiding the development of cancer interception and prevention strategies.